Longitudinal analysis of the quality of orthodontic treatment outcome and stability of occlusal traits - Arponen Heidi; Suominen Auli; Svedström-Oristo Anna-Liisa (Taylor & Francis, 2022)
Objectives
To assess the quality and stability of orthodontic treatment outcome relative to the initial malocclusion.
Material and methods
The study was performed in one public health care clinic in Finland. Study subjects comprised 51 orthodontic patients (age range 12.7–18.7 years). Pre-treatment medical records and lateral skull radiographs were analysed for malocclusion type. The main reasons for orthodontic treatment were mandibular retrognathia, Class II distal bite, deep bite and crowding. At the end of a retention phase (Examination 1), the quality of treatment outcome was assessed using the occlusal morphology and function index (OMFI) and patients were asked about treatment satisfaction. Stability of occlusal traits and patient satisfaction were re-evaluated after a two-year follow-up (Examination 2). Occlusal characteristics descriptive statistics were performed.
Results
At Examination 1, all six morphological criteria for acceptability were fulfilled by 76% and all functional criteria by 82% of the patients. All OMFI criteria were met by 67% of the patients. At Examination 2, 68% of the patients fulfilled all morphological and 82% all functional criteria of acceptability. At Examination 2, all the OMFI criteria were still met by 64% of the patients and 92% expressed satisfaction with own occlusion. The main reasons for unacceptability were deficiencies in canine relationship and overbite, in addition to functional protrusion interferences.
Conclusions
In the evaluated health care clinic, patient satisfaction and the quality of treatment outcome were high. However, deep bite showed a tendency for relapse.